Enhancing EFL Students’ Learning Motivation through Digital Game-Based Learning: A Classroom Action Research Study - Hastuti Rahmah; Ari Purnawa (Journal of Innovation and Research in Primary Education, 2026)
Learning motivation plays a crucial role in successful English as a Foreign Language (EFL) learning; however, many secondary school students experience low motivation due to limited engagement in conventional instructional practices. This study investigates the use of digital game-based learning to enhance students' motivation in an EFL classroom through a mixed-method Classroom Action Research design. The intervention was implemented across three iterative instructional cycles involving eighth-grade students at a junior secondary school. Quantitative data were collected using a learning motivation questionnaire, while qualitative data were obtained through classroom observations and semi-structured interviews. The findings indicate a consistent improvement in students' learning motivation, accompanied by increased engagement, confidence, and active participation throughout the cycles. The novelty of this study lies in its integration of digital game-based learning within a cyclical Classroom Action Research framework to capture the dynamic development of EFL learners' motivation over time, rather than measuring it at a single point in time. The results provide empirical evidence that digital game-based learning can serve as a sustainable pedagogical strategy for fostering motivated and engaged EFL learners in authentic classroom contexts, with practical implications for secondary-level English instruction.